2018
DOI: 10.2463/mrms.mp.2017-0072
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Tumors of the Bone: Changes in Image Features after Denosumab Administration

Abstract: Purpose:To assess the clinical importance in the feature change in giant cell tumors of the bone (GCTB) after denosumab treatment, detected by MRI.Methods:In 12 patients, MRI and CT of GCTB obtained before and after the treatment retrospectively compared. The tumor size, the signal intensity (SI) ratio between the solid part of the GCTB and muscle, cystic part size, gadolinium enhancement and apparent diffusion coefficient (ADC) value were measured on MRI. The bone formation in the tumor was observed on CT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
5
11
0
Order By: Relevance
“…In accordance with our experience, Oguro et al concluded that both shrinkage of the cystic component in the tumour and a decrease in T2 signal intensity (representing new bone formation) are more useful markers to assess treatment response [33]. Contrast enhancement and DWI/ADC were not found particularly useful; however, the study included only a small number of patients (N = 12) [33]. More research is needed to evaluate the value of contrast enhancement studies before and after denosumab treatment, as dynamic contrast enhancement (mean time intensity curves) may add more information [34].…”
Section: Magnetic Resonance Imagingsupporting
confidence: 87%
See 3 more Smart Citations
“…In accordance with our experience, Oguro et al concluded that both shrinkage of the cystic component in the tumour and a decrease in T2 signal intensity (representing new bone formation) are more useful markers to assess treatment response [33]. Contrast enhancement and DWI/ADC were not found particularly useful; however, the study included only a small number of patients (N = 12) [33]. More research is needed to evaluate the value of contrast enhancement studies before and after denosumab treatment, as dynamic contrast enhancement (mean time intensity curves) may add more information [34].…”
Section: Magnetic Resonance Imagingsupporting
confidence: 87%
“…Decreased T2-weighted MR signal has previously been described [4,11,21,33] with demonstrable signal change from 7 weeks [11] after commencing denosumab treatment.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 79%
See 2 more Smart Citations
“…This may be explained as increased water diffusivity due to tissue necrosis, which is the same response to chemotherapy as seen in other malignant bone tumors. In a study of GCT, although only six subjects were evaluated, changes in ADC after denosumab treatment varied . The authors suggested that denosumab induced a variable histological response like that of intermixed bone and fibroblast‐like spindle cells or dense calcification might limit the potential use of ADC.…”
Section: Apparent Diffusion Coefficient (Adc)mentioning
confidence: 99%